Hospital organizational change: The importance of teamwork culture, communication, and change readiness - Ellis, Louise A.; Tran, Yvonne; Pomare, Chiara; Long, Janet C.; Churruca, Kate; Saba, Maree; Braithwaite, Jeffrey (Frontiers in Public Health, 2023)
Background Hospital organizational change can be a challenging time, especially when staff do not feel informed and ready for the change to come. A supportive workplace culture can mitigate the negative effects allowing for a smooth transition during hospital organizational change. In this paper, we test an exploratory path model by which teamwork culture influences staff attitudes in feeling informed and ready for change, and which are ultimately related to reduced staff burnout. We also examined different types of change communication, identifying the channels that were perceived as most useful for communicating organizational change. Methods In 2019, a cross-sectional online and paper-based survey of all staff (clinical and non-clinical) was conducted at a hospital undergoing major organizational change in Sydney, Australia. The survey included items regarding teamwork culture, communication (feeling informed, communication channels), change readiness (appropriateness, change efficacy), and burnout. With a sample size of 153 (62% clinical staff), regression and path analyses were used to examine relationships between variables. Results The total effects between teamwork culture and burnout was significant [β (Total) = −0.37, p < 0.001) and explained through a serial mediation. This relationship was found to be mediated by three factors (feeling informed, appropriateness of change and change efficacy) in a full mediation. Further, change readiness (appropriateness of change and change efficacy) mediated the relationship between feeling informed and burnout. The most useful channels of change communication included face-to-face informal communication, emails, and a newsletter specifically about the change. Conclusion Overall, the results supported the predicted hypotheses and were consistent with past research. In the context of large hospital change, staff with a positive teamwork culture who feel informed are more likely to feel change-ready, heightening the chances of successful organizational change and potentially reducing staff burnout. Understanding the pathways on how culture and communication related to burnout during organizational change provides an explanatory pathway that can be used to heighten the chances of a smooth change transition with minimal disruption to staff and patient care.